CHILDHOOD AND LITERACY (A CRITICAL STUDYOF MEDIA EDUCATION AS CONTEMPORARY CULTURE) - Annury, Muhammad Nafi (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2015)
Childhood is the phase of where the human beginning to learnabout its surrounding obviously. This phase needs more attentionfrom us as parent however, to make sure that our children keep inthe right path of their development. Therefore, the development ofICT brings many consequences in every aspect of our life; and thiscondition has infl uenced too toward children development anyway.Based on this phenomenon, the writer would like to introduce someproblems relate with childhood and literacy. The literacy of usingthe media education, therefore, teacher and parents should be con-cerned about it to the children. Teacher and parents however, theyhave to give better guidance to children relate with may informa-tion and ICT which are used in the classroom or at home. Childrenshould be given better understanding by teacher and parents every-time they need information. Some experts say that media can givepositive and negative effect obviously. Thus, the writer hopes thatmay give any review by this article.